The impact of selected heavy metals to dyspermia in Nigeria (2014)
Declining male fertility is of global concern and has been linked to the effects of some heavy metals which are recognised as testicular toxins. Selenium and zinc play specific roles in heavy metal detoxification, testosterone metabolism, sperm formation and motility. This study was aimed at identifying the possible contribution of cadmium (Cd), lead (Pb), selenium (Se) and zinc (Zn) to sperm defects in Nigerian men. 120 males (20-54 years) were recruited after informed consent. These were age-matched 77 dyspermics and 43 normospermics. Semen samples were collected from subjects by masturbation after 3-5 days of abstinence from sexual intercourse. Spermiogram and sperm morphological characteristics were done using WHO guidelines and Tygerberg Strict criteria respectively. 10 ml of blood was obtained from each participant. Serum and seminal plasma were obtained by centrifugation of clotted blood and semen respectively. Cd, Pb, Se and Zn were assayed in serum and seminal plasma by atomic absorption spectrophotometry. Data were analysed using t-test, ANOVA and multiple regressions at p=0.05. Increased serum Zn/Cd (p=0.04) and Se/Cd (p=0.03) significantly predicted increased semen volume in dypermics. Increased seminal plasma Se/Pb (p=0.05) significantly predicted increased normal sperm morphology. Increased serum Cd significantly predicted increased tail defects (p=0.008) whereas, increased serum Se/Cd significantly predicted decreased tail defects (p=0.01) in normospermics only. Increased serum Zn/Cd significantly predicted (p=0.048) decreased Teratozoospermia index (TZI). Increased seminal plasma Zn (p=0.04) and Zn/Pb (p=0.04) significantly predicted decreased sperm deformity index (SDI) respectively. Reduced levels of selenium and zinc in dyspermic males may account for the loss of their protective effect against cadmium and lead toxicity to the testes.